ANALYSIS OF THE FUNCTIONAL CHARACTERISTICS OF ANTHROPONYMS IN THE CONTEXT OF THE NOVEL BEING HUMAN IS DIFFICULT - S.B.Khursankulov; D.Z.Abduazimova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the functional aspects of anthroponyms used in O‘lmas Umarbekov’s novel “Odam bo‘lish qiyin” and highlights their role in portraying character traits. In addition, the author’s individual skill in selecting names is examined and evaluated. The results of the study contribute to enriching the theoretical and practical foundations of ongoing and future research in the fields of literary text linguistics and onomastics.